TUNAS JAYA VILLAGE COMMUNITY EMPOWERMENT METHOD BONEPANTAI DISTRICT, BONE BOLANGO REGENCY - djafar umati; titin dunggio; karlina napu (LP2M Universitas Bina Mandiri Gorontalo, 2024)
This study aims to determine how big the influence of Community Empowerment in Tunas Jaya Village, Bonepantai District, Bone Bolango Regency. Empowerment of rural communities is a basic effort of local government officials and the central government, especially towards a potential that exists in the village as a form of assets or wealth owned by the village. This study focuses more on knowing how much potential community development resources exist in Tunas Jaya Village, Bone Coast District, Bone Bolango Regency. In this study using descriptive qualitative research methods conducted in the field (field research), where the total population of 200 people and 5 samples, people using purposive sampling in determining the sample. While the data collection tool in this study uses an inductive method, namely how to draw conclusions from specific things to general things, this research is a field research which can find out the specifics and the reality of what is happening in the community. The problem of this research is how business groups can build Tunas Jaya Village, Bonepantai District, Bone Bolango Regency in the field of entrepreneurship.